Differential tt¯ $$ t\overline{t} $$ cross-section measurements using boosted top quarks in the all-hadronic final state with 139 fb −1 of ATLAS data. (Tufts University. Tisch Library., 2023)
Keywords : Hadron-Hadron Scattering, Jet Substructure and Boosted Jets, Top Physics.; Springer Open.